The Influence of an Information Environment on Construction Organization's Culture: A Case Study - Kenneth T. Sullivan; Dean T. Kashiwagi; Nathan Chong (Advances in Civil Engineering)
Construction professionals have identified public contract law and bureaucratic procurement/contract offices as a source of problems in the construction industry. The culture within the United State's Federal Government Acquisitions is based on the Federal Acquisition Regulations (FARs) and its interpretation, often placing organizations/agencies in the price-based environment and continuously resulting in poor performance. The United States Army Medical Command (MEDCOM) (approximately $100 M in construction renovation awards per year) attempted to overcome this obstacle through a partnership with the Performance-Based Studies Research Group (PBSRG) at Arizona State University. The MEDCOM implemented the information environment portion of the Performance Information Procurement System (PIPS) into Indefinite Delivery Indefinite Quantity (IDIQ) contracts through the specifications. Without controlling the various contract/procurement processes, the developed information environment stimulated an atmosphere of accountability to all parties involved, while reducing the client's internal bureaucratic resistance. The concept has met with preliminary success, minimizing construction management issues by over 50%, raising owner satisfaction by 9%, resulting in 99% of projects ending with no contractor-generated change orders, and assisting MEDCOM leadership in measuring the performance of their infrastructure revitalization program.